Efficacy and Safety of Iclaprim for the Treatment of Skin Structures and Soft Tissue Infections: A Methodological Framework - Wang, Lian; Fan, Jin; Zheng, Linli; Chen, Lingmin (Frontiers in Pharmacology, 2022)
Abstract Background: Skin and soft tissue infections (SSTIs) are among the most common infections worldwide. It manifests in a variety of forms, such as erysipelas, cellulitis and necrotizing fasciitis. Antibiotics are the significant method for clinical treatment of SSTIs. This study aimed to determine the efficacy and safety of iclaprim for the treatment of SSTIs. Methods: We will search the PubMed, EMbase, CNKI, WanFang Data, VIP, CBM, Web of Science and ClinicalTrials.gov from their inception to June 2022 for randomized controlled trials (RCTs) and cohort studies about the iclaprim with SSTIs. Two authors will independently screen the eligible studies, assess the quality of the included papers and extract the required information. Randomized controlled trials will be assessed with the Cochrane risk-of-bias tool. The Newcastle-Ottawa Scale will be used to evaluate observational studies. We will evaluate the quality of the evidence through Grading of Recommendations Assessment Development and Evaluation (GRADE) system. RevMan 5.3 will be used for the data synthesis and quantitative analysis. Results and discussions: This study will provide the clinicians with more high-quality evidence to choose iclaprim for patients with skin and soft tissue infections. Ethics and dissemination: This systematic review and meta-analysis will be based on published data, so ethical approval is not necessary. The results of this meta-analysis will be published in a peer-reviewed journal. PROSPERO registration number: CRD42018107278. (URL: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42018107278)